Pelatihan Pemanfaatan Aplikasi Qasir Pada UMKM Zulichcare Dan Bon’s Laundry Demi Meningkatkan Pencatatan Akuntansi - Dzulfikri Rizqullah; Hasim As’ari (Jurnal Mutiara Ilmu Akuntansi, 2024)
The economic sector plays a key role in the well-being of the Indonesian society. The increasingly competitive economic growth poses challenges for Micro, Small, and Medium Enterprises (MSMEs) in recording financial transactions. This research aims to engage business practitioners in adapting to the development of digital technology through training on the usage of the Qasir Point of Sales application. This application is designed to facilitate business owners who want to manage their businesses digitally more easily. The research methodology involves three stages: preparation, including an in-depth analysis of the specific needs of MSMEs related to accounting and the use of the Qasir application; implementation, with direct assistance in creating and configuring the Qasir application to ensure alignment with the specific business needs of the two MSMEs; and evaluation, ensuring a good understanding and measuring the impact of the training. The conclusion emphasizes the success of the training and the importance of continuous adaptation to technological and business developments. It is expected that this will have a positive impact in supporting efficient and sustainable accounting records in UMKM Zulich Clean and Care and Bon’s Laundry.